2006
DOI: 10.4049/jimmunol.176.7.3909
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: B and T Lymphocyte Attenuator and Programmed Death Receptor-1 Inhibitory Receptors Are Required for Termination of Acute Allergic Airway Inflammation

Abstract: T cell activation is regulated by coordinate interaction of the T cell Ag receptor and costimulatory signals. Although there is considerable insight into processes that regulate the initiation of inflammation, less is known about the signals that terminate immune responses. We have examined the role of the inhibitory receptors programmed death receptor-1 and B and T lymphocyte attenuator in the regulation of allergic airway inflammation. Our results demonstrate that there is a temporally regulated expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
73
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 16 publications
4
73
0
Order By: Relevance
“…This finding is consistent with already published data showing that BTLA is induced upon TCR-mediated stimulation of T cells in vitro (20). Recently, it has been shown in vivo that BTLA contributes to the termination of allergic airway inflammation because BTLA-deficient mice exhibit a prolonged infiltration of lymphocytes and eosinophils in bronchoalveolar lavage fluid (22). During blood-stage PbA infection, we found that BTLA expression on splenic CD4 ؉ as well as CD8 ϩ T cells increased during the course of disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with already published data showing that BTLA is induced upon TCR-mediated stimulation of T cells in vitro (20). Recently, it has been shown in vivo that BTLA contributes to the termination of allergic airway inflammation because BTLA-deficient mice exhibit a prolonged infiltration of lymphocytes and eosinophils in bronchoalveolar lavage fluid (22). During blood-stage PbA infection, we found that BTLA expression on splenic CD4 ؉ as well as CD8 ϩ T cells increased during the course of disease.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the role of BTLA as a negative receptor, mice lacking the full-length form of BTLA are hyperresponsive to TCR-mediated activation of T cells (15). In acute allergic airway inflammation, BTLA in combination with PD-1 contributes to the termination of this TH2-mediated immune response, because mice lacking these receptors show prolonged lung inflammation (22). Moreover, it has been demonstrated in an in vivo transplantation model that BTLA is involved in the acceptance of partially MHC-mismatched cardiac allografts (23).…”
mentioning
confidence: 74%
“…BTLA is a coinhibitory receptor with structural similarities to CTLA-4 and PD-1, and the negative cosignaling role of BTLA is supported by observations of attenuated lymphocyte responses after in vitro cross-linking (20). Although BTLA-deficient mice have normal B and T cell development, these mice have exacerbated responses in the experimental autoimmune encephalomyelitis model (16) and worse disease in a model of allergic airway inflammation (21). BTLA targeting has been implicated in the accelerated rejection of partially mismatched cardiac grafts but also in prolongation of fully-mismatched allografts (22), and we hypothesize that BTLA negative cosignaling may be important in the context of costimulatory blockade in islet allograft survival.…”
Section: Introductionmentioning
confidence: 97%
“…Initially, we have shown that the sensitivity to experimental autoimmune encephalomyelitis as well as T cell-dependent Ab responses is increased in BTLA 2/2 mice (3). It has also been reported that BTLA 2/2 mice exhibit a rapid rejection of partially MHC-mismatched cardiac allograft (9), persistent allergic airway inflammation following Ag challenge (10,11), and an acceleration of experimental colitis (12). These findings indicate that BTLA is crucial for dampening immune responses mediated by T cells.…”
mentioning
confidence: 84%